An encapsulated helical one-dimensional cobalt iodide nanostructure. - Philp, E; Sloan, J; Kirkland, A; Meyer, R; Friedrichs, S; Hutchison, J; Green, M (2003)
Single-walled carbon nanotubes (SWNTs) can be used as templates for the growth of low-dimensional inorganic materials whose structures and properties often differ greatly from those of the bulk. Here we describe the detailed crystallography of an entire helical one-dimensional cobalt diiodide nanostructure encapsulated within a SWNT. This material has an unprecedented twisted double tetrahedral chain structure arising from a rotation of Co(2)I(4) units along its length. The complete nanostructure comprises two distinct regions with oppositely handed helices separated by a short disordered region. The encapsulating SWNT shows a commensurate ovoid distortion reflecting an unexpectedly strong interaction between the nanostructure and the SWNT.